2021
DOI: 10.3390/polym13020237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Raster Angle and Moisture Content on the Mechanical Properties of PLA Parts Produced by Fused Deposition Modeling

Abstract: The additive manufacturing (AM) processes and technologies of 3D-printed materials and components using fused deposition modeling (FDM) are currently very popular and widely used for building parts and prototypes. Many manufacturing parameters can affect the strength and strain of the manufactured parts. The manufacturing parameters may be altered to reach an optimum setting for highly effective parts or components. This research studies the influence of the raster angle and the moisture content percentages on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 34 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…At low humidity, PLA has higher mechanical strength but lower toughness [ 36 ]. In [ 37 ] it is shown that reducing moisture content from 10% to 1% results in a decrease in the tensile strength with 24.4%.…”
Section: From Pre-process Conditions To Mechanical Characterization O...mentioning
confidence: 99%
“…At low humidity, PLA has higher mechanical strength but lower toughness [ 36 ]. In [ 37 ] it is shown that reducing moisture content from 10% to 1% results in a decrease in the tensile strength with 24.4%.…”
Section: From Pre-process Conditions To Mechanical Characterization O...mentioning
confidence: 99%
“…Few references regarding the analysis of 3D printed parts or specimens in highmoisture environments have been found in the literature. To highlight the research of Algarni [15], which presents a study describing the effect of moisture and raster orientation in the mechanical properties of polylactic acid (PLA) specimens. Results show 10% of moisture in specific raster orientations improves mechanical and strength properties.…”
Section: Introductionmentioning
confidence: 99%
“…The current levels of researches and developments in polymers such as ABS (Ref 17 -19), PLA (Ref 20-23), polyamide (Ref 24,25), high-density polyethylene (HDPE) (Ref 26), polycarbonate (PC) (Ref 27), and polyurethane (PU) (Ref 28) are manufactured using FDM have generated extra opportunities for discovering potential applications for AM/ 3DP techniques. In contrast, strong dependence of properties on printing parameters has made it a major subject of researches in this field, despite the passage of several years.…”
Section: Introductionmentioning
confidence: 99%